The Vote Is Cast: The Effect of Corporate Governance on Shareholder Value - CUÑAT, VICENTE; GINE, MIREIA; GUADALUPE, MARIA (Journal of Finance, 2012)
ABSTRACT This paper investigates whether improvements in the firm's internal corporate governance create value for shareholders. We analyze the market reaction to governance proposals that pass or fail by a small margin of votes in annual meetings. This provides a clean causal estimate that deals with the endogeneity of internal governance rules. We find that passing a proposal leads to significant positive abnormal returns. Adopting one governance proposal increases shareholder value by 2.8%. The market reaction is larger in firms with more antitakeover provisions, higher institutional ownership, and stronger investor activism for proposals sponsored by institutions. In addition, we find that acquisitions and capital expenditures decline and long‐term performance improves.